Catheter directed pulmonary artery thrombolysis in a Covid-19 positive patient with massive pulmonary embolism: Case management and endovascular suite workflow in a pandemic - Rajadurai, Arvin; Abdul Ghani, Zulkifli Zaki; Eng, Kar Seng; Rosnani, Emy Saera (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
Thromboembolic complications are common complications amongst cases of COVID-19 worldwide. This occurrence has seen a key role of endovascular treatment in managing this potentially fatal complication. Endovascular thrombectomy or catheter directed thrombolysis is a fast and effective method for treatment of pulmonary embolisms, especially in the setting of a pandemic. However, good workflow and safety measures should be strictly adhered to ensure a favorable outcome of patients and ensure safety of treating personnel.